2023
DOI: 10.1371/journal.pone.0283565
|View full text |Cite
|
Sign up to set email alerts
|

Age and gender effects on presence, user experience and usability in virtual environments–first insights

Abstract: Virtual Reality (VR) is applied in various areas were a high User Experience is essential. The sense of Presence while being in VR and its relation to User Experience therefore form crucial aspects, which are yet to be understood. This study aims at quantifying age and gender effects on this connection, involving 57 participants in VR, and performing a geocaching game using a mobile phone as experimental task to answer questionnaires measuring Presence (ITC-SOPI), User Experience (UEQ) and Usability (SUS). A h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 55 publications
(93 reference statements)
0
1
0
Order By: Relevance
“…This finding seems to diverge from previous studies that suggest potential gender differences in VR learning environments [29][30][31]. However, it is important to note that research on gender and age effects in VR environments is still limited and urgently needed [32].…”
Section: What Explains How Different Students Evaluate the Vr Workhop?contrasting
confidence: 73%
“…This finding seems to diverge from previous studies that suggest potential gender differences in VR learning environments [29][30][31]. However, it is important to note that research on gender and age effects in VR environments is still limited and urgently needed [32].…”
Section: What Explains How Different Students Evaluate the Vr Workhop?contrasting
confidence: 73%
“…Interestingly, in the entire sample, the level of education emerged as a factor influencing the perception of usability of the immersive virtual reality (iVR) system. Notably, age did not negatively impact the usability perception of iVR, as noted by Lorenz and colleagues (2023), who found a correlation between age and System Usability Scale (SUS) results regarding iVR [ 35 ].…”
Section: Discussionmentioning
confidence: 86%
“…Finally, age and gender can also affect presence, user experience, and usability in VR [33]. A study involving 57 participants in VR found that older participants had a higher sense of presence than younger participants [34]. However, there were no gender differences or interaction effects of age and gender.…”
Section: Factors Affecting User Experience In Virtual Environmentsmentioning
confidence: 99%